Bioremediation of petroleum hydrocarbon contaminated soil: a review on principles, degradation mechanisms, and advancements - Mekonnen, Bassazin Ayalew; Aragaw, Tadele Assefa; Genet, Melkamu Birlie (Frontiers in Environmental Science, 2024)
Petroleum hydrocarbons (PHCs) are key energy sources for several industries and daily life. Soil contamination from oily PHC spills is commonly detected in cities and industrial facilities where crude oil is used. The release of PHC pollutants into the environment, whether accidentally from petroleum industries or human activities, has become a leading source of soil pollution. Consequently, the mineralization of PHC-polluted sites has become a central issue worldwide. Although bioremediation is imperative for environmental safety and management, several approaches have been developed for PHC bioremediation. However, much remains to be explored in this regard. This review explores bioremediation of PHC-contaminated soil and provides a comprehensive examination of the principles, degradation mechanisms, and recent advancements in the field. Several microbial species have been used to study the bioremediation of PHCs, emphasizing the pivotal roles of diverse microbial communities. Aspergillus spp., Proteobacteria, and Firmicutes groups of microorganisms were the most efficient in remediating PHC-contaminated soil. The fundamental concepts behind the bioremediation of PHC and the complex mechanisms that govern degradation were elucidated. Limiting factors in the bioremediation process and recent innovations propelling the field were also discussed. Therefore, understanding the degradation pathway, ensuring complete degradation of contaminants, and flexible legislation for the proper use of genetically engineered microbes can make bioremediation more sustainable and cost-effective.